THE JAVANESE MYTH AMONGS THE MODERN PEOPLE IN 2000s GENERATION - Sahid; M. Elfan Kaukab (SABBHATÃ YATRA : Jurnal Pariwisata dan Budaya, 2022)
This study aims at investigating the Javanese myth among the modern people in 2000s generation. This study focuses on the area of Wonosobo Regency to be observed. The researcher conducted the in-depth interview toward the stake holder (Sesepuh/traditional leader, the residents); observation, documentation and giving questionnaires also conducted to obtain the validity of data. The result of this study shows there are various perception and attitudes toward the existence of Javanese myth among them and there are some kinds of myth that still believed. The Javanese myth still exist among the modern people in the area of Wonosobo.